PROBLEMS THROUGH A GREEN ECONOMIC SYSTEM APPROACH - Pebrian, Aldi; Vivi Yulianingrum, Aullia; Ayu Hasmiati, Rahmatullah; Elviandri, Elviandri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Economic development will develop quickly if a green economic system is adopted. a green economic system that is oriented towards the relationship between ecosystem nature and the presence of human resource elements by prioritizing knowledge and technology. Changes in the economy from previously only about profit and welfare to a green economy that has environmental principles. Samarinda, as a supporting city for IKN, is one of the cities in East Kalimantan Province which is the center of attention for rice competitions. It cannot be denied that many immigrants who come do not bring the skills to become PMKS in Samarinda City. Referring to the principles of a green economy, namely prioritize quality, follow nature, waste can be recycled etc. The problem formulation of this research is regarding the legal arrangements for handling and handling empowerment people with social welfare problems in the form of policing in green spaces and what form of policy the Samarinda City Government takes in empowering people with social welfare problems through a green economy approach that prioritizes a livable city structure. The aim of this research is to find out legal regulations from an administrative and criminal perspective even civil law due to the relationship between the Samarinda City Government and the Community Incumbent Social Welfare Issues. Apart from that, to analyze the policy formulation of the Samarinda City government which prioritizes structuring room cities to reduce the risk of environmental damage. The conclusion of this research is that in terms of the legal structure it is adequate, where the Samarinda City Social Service is to assist in terms of empowerment while the Satpol-PP is tasked with carrying out handling. Substance the law is still there Not yet adequate, one of which is that the old regional regulations are still used and there are no guardians. Meanwhile, legal culture is also becoming Wrong Where is education for the community so that not giving money to PMKS and the lack of deterrent not giving money to PMKS and the lack of deterrent effect on those who have received training.